Ecological aspects of structural change - Martin Jänicke; Harald Mönch; Manfred Binder (Intereconomics, 1993)
Structural change in advanced industrialized countries has followed a very ambivalent course, with the resulting reductions in environmental stress in one area often being cancelled out by increases in another. What role has been played in this to date by industrial and economic policy? What options are open to policy-makers for the future?
Keywords: 330; Environmental Policy